2003
DOI: 10.1093/brain/awg248
|View full text |Cite
|
Sign up to set email alerts
|

Ventral occipital lesions impair object recognition but not object‐directed grasping: an fMRI study

Abstract: D.F., a patient with severe visual form agnosia, has been the subject of extensive research during the past decade. The fact that she could process visual input accurately for the purposes of guiding action despite being unable to perform visual discriminations on the same visual input inspired a novel interpretation of the functions of the two main cortical visual pathways or 'streams'. Within this theoretical context, the authors proposed that D.F. had suffered severe bilateral damage to her occipitotemporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
329
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 495 publications
(357 citation statements)
references
References 43 publications
19
329
1
1
Order By: Relevance
“…(Faillenot et al, 1997;James et al, 2003). These investigations indicate that object-oriented action and object recognition activate a common posterior parietal area.…”
Section: Introductionmentioning
confidence: 63%
“…(Faillenot et al, 1997;James et al, 2003). These investigations indicate that object-oriented action and object recognition activate a common posterior parietal area.…”
Section: Introductionmentioning
confidence: 63%
“…With respect to area V5, Schenk et al (2005) found that magnetic stimulation here can lengthen the execution of the action of catching a moving object. In contrast, a combined neuropsychological and fMRI study by James et al (2003) shows a clear dichotomy between the ventral and dorsal streams for object recognition and object directed grasping. Nevertheless, in normal human subjects a much more integrative approach may be involved in processing tasks like the present one, in which reciprocal interactions which involve earlier perceptual processes may be concerned either with perceptual issues or response issues in the task.…”
Section: Discussionmentioning
confidence: 85%
“…It is also possible that magnetically induced stimulation of both LO and PPC are impeding, and therefore slowing down, preparation for a motor response. The role of the dorsal stream in visuomotor transformations is clear from neuropsychological (James et al, 2003), functional imaging (Culham et al, 2006) and TMS (Ellison et al, 2003) studies. But this alone does not explain the involvement of PPC in the visuospatial task used in this study as PPC was not involved in a shape discrimination where the same visuomotor transformation was required in our previous paper (Ellison & Cowey 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our research group had the opportunity to perform additional MRI and fMRI scans of D.F. in 2001 (Culham, 2004;James et al, 2003). An examination of the anatomical MRI images suggested three main lesions, one in the lateral occipital (LO) cortex of each hemisphere and one in the left hemisphere near the top of the parietooccipital sulcus.…”
mentioning
confidence: 99%
“…An examination of the anatomical MRI images suggested three main lesions, one in the lateral occipital (LO) cortex of each hemisphere and one in the left hemisphere near the top of the parietooccipital sulcus. The location in stereotaxic space (Talairach & Tournoux, 1988) (James et al, 2003). Although D.F.…”
mentioning
confidence: 99%